Regional Developments: An Uneven and Uncertain Recovery. Issue 1 (January 2015) - Andrianov, Vladimir; Bourmpoula, Valia; Chacaltana, Juan; Dasgupta, Sukti; Duda, Marta; Ernst, Ekkehard; Haidar, Salwa; Horne, Richard; Huynh, Phu; Jafaar, Aya; Khatiwada, Sameer; Kim, Kee Beom; et al.
Abstract : The chapter gives a detailed overview of recent labour market trends across eight major world regions. The chapter discusses each one of them, highlighting the divergent trends both within and across regions. In particular, the continuous improvement in some major advanced economies contrasts sharply with the ongoing difficulties in many European countries and the first signs of slowdown in key emerging markets.